Effects of thermal exposure on the microstructure and mechanical properties of Al-12Si-4Cu-1Ni-1Mg-2Mn piston alloys. (1st November 2020) - Lin, Bo; Xia, Songchao; Tang, Yue; Zhao, Yuliang; Liu, Kun; Xiao, Huaqiang; Li, Shaobo; Zhang, Weiwen
ABSTRACT: The effect of thermal exposure on the elevated-temperature mechanical properties of heat-treated Al-12Si-4Cu-1Ni-1 Mg-2Mn piston alloys was investigated using optical microscopy (OM), scanning electron microscope (SEM), transmission electron microscopy (TEM), and tensile tests at elevated temperatures. The results showed that coarsening of the strengthening precipitates following a prolonged exposure at 350°C had a deleterious effect on the elevated-temperature tensile properties. Further thermal exposure up to 50 h did not result in even a slight reduction in the strength. After exposure at 350°C, the value of elevated-temperature ultimate tensile strengths of Al-12Si-4Cu-1Ni-1 Mg-2Mn piston alloys were 92, 80, and 73 MPa for 0 h, 10 h, and 100 h of thermal exposure, respectively, which are superior to those of the commercial piston alloys. The high-performance, elevated-temperature mechanical properties of Al-12Si-4Cu-1Ni-1 Mg-2Mn piston alloys can be attributed to the high thermal stability Mn-rich intermetallics and Al3 CuNi.